Thematic progression and rhetorical structure in opinion articles of an online Iraqi English newspaper / Nadia Abed Shakeh - Abed Shakeh, Nadia (2014)
This study examines how the Iraqi writers maintain cohesion in the text by analyzing the patterns of thematic progression in various rhetorical moves in an online Iraqi newspaper, Azzaman (Zaman). This study integrates two theoretical frameworks such as the rhetorical movement which was modified by Van Dijk (1993) and later modified by Katajamaki and Kosketa (2006) and the thematic progression theory by Danes (1974). From that perspective, this study aims to examine the rhetorical patterns and the occurrence of thematic progression of Azzaman Iraqi newspaper’s opinion articles. To carry out the study, twelve (12) opinion articles from Azzaman’s English edition, published from January 2013 to June 2013 were collected and analyzed. The analysis focused on the rhetorical structures and thematic progression. The findings reveal the patterns of rhetorical structure used in Azzaman’s opinion articles and the thematic progression patterns used in every rhetorical section. The findings further reveal that the introduction, intermediate (intermediate stage) and coda section (conclusion stage) are commonly used while the used intermediate section (solution stage) and coda section (moral stage) are least used. On the other hand, it is also evident that in every section of the rhetorical structure there is an occurrence of different thematic progressions. The findings show that simple linear theme progression and constant theme progression occur the most. However, there are similarities in the absence of split rheme progression in all texts. The findings further reveal that rhetorical structure section is used in three sections in most articles, but differ greatly in the aspect of solution and moral stage. It turns out that most of the articles that were examined do not have solution and moral stages.